IMF Staff papers : Volume 12 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1965)
This paper reviews an attempt that is made to arrive at a rough quantification of the possible effects of various techniques of IMF reserve creation through the IMF on its own liquidity. For purposes of comparison, the additional needs for IMF resources arising, respectively, from the several techniques of reserve creation are expressed in terms of the amounts of the currencies that are normally suitable for drawing, distributed in proportion to quota, to which the IMF would have to secure to cover the additional needs in question. When reserves are created by the IMF, their creation will in some instances involve a use of Fund resources and may affect its own liquidity. When account is taken of the secondary impact of gold investment on world reserves, it appears that the liquidity cost to the IMF of creating reserves by means of gold investment, though greater per unit of investment, might be somewhat less per unit of reserves created than that of other forms of investment.